Heavy Current Static Machines - Central Scientific Company (Physical Apparatus for Universities and Colleges Manufactured and Imported by Central Scientific Co., 1912)
Catalog entry for a heavy current static machine. Part of Catalog K: Physical Apparatus for Universities and Colleges, a catalog of laboratory instruments for the physical sciences made by the Central Scientific Company. Founded in 1900 in downtown Chicago, Central Scientific manufactured and distributed science teaching equipment for schools, colleges, and universities by catalog mail order. The trademark CENCO was used from 1909 onwards.
Keywords: Scientific apparatus and instruments; Laboratories--Equipment and supplies; Electrostatic accelerators